Three‐year quantitative magnetic resonance imaging and phosphorus magnetic resonance spectroscopy study in lower limb muscle in dysferlinopathy. Issue 3 (3rd April 2022) - Reyngoudt, Harmen; Smith, Fiona E.; Caldas de Almeida Araújo, Ericky; Wilson, Ian; Fernández‐Torrón, Roberto; James, Meredith K.; Moore, Ursula R.; Díaz‐Manera, Jordi; Marty, Benjamin; Azzabou, Noura; Gordish, Heather; Rufibach, Laura; et al.
Abstract: Background: Natural history studies in neuromuscular disorders are vital to understand the disease evolution and to find sensitive outcome measures. We performed a longitudinal assessment of quantitative magnetic resonance imaging (MRI) and phosphorus magnetic resonance spectroscopy ( 31 P MRS) outcome measures and evaluated their relationship with function in lower limb skeletal muscle of dysferlinopathy patients. Methods: Quantitative MRI/ 31 P MRS data were obtained at 3 T in two different sites in 54 patients and 12 controls, at baseline, and three annual follow‐up visits. Fat fraction (FF), contractile cross‐sectional area (cCSA), and muscle water T2 in both global leg and thigh segments and individual muscles and 31 P MRS indices in the anterior leg compartment were assessed. Analysis included comparisons between patients and controls, assessments of annual changes using a linear mixed model, standardized response means (SRM), and correlations between MRI and 31 P MRS markers and functional markers. Results: Posterior muscles in thigh and leg showed the highest FF values. FF at baseline was highly heterogeneous across patients. In ambulant patients, median annual increases in global thigh and leg segment FF values were 4.1% and 3.0%, respectively ( P < 0.001). After 3 years, global thigh and leg FF increases were 9.6% and 8.4%, respectively ( P < 0.001). SRM values for global thigh FF were over 0.8 for all years. Vastus lateralis muscle showed the highest SRM values across all time points. cCSA decreased significantly after 3 years with median values of 11.0% and 12.8% in global thigh and global leg, respectively ( P < 0.001). Water T2 values in ambulant patients were significantly increased, as compared with control values ( P < 0.001). The highest water T2 values were found in the anterior part of thigh and leg. Almost all 31 P MRS indices were significantly different in patients as compared with controls ( P < 0.006), except for pHw, and remained, similar as to water T2, abnormal for the whole study duration. Global thigh water T2 at baseline was significantly correlated to the change in FF after 3 years ( ρ = 0.52, P < 0.001). There was also a significant relationship between the change in functional score and change in FF after 3 years in ambulant patients ( ρ = −0.55, P = 0.010). Conclusions: This multi‐centre study has shown that quantitative MRI/ 31 P MRS measurements in a heterogeneous group of dysferlinopathy patients can measure significant changes over the course of 3 years. These data can be used as reference values in view of future clinical trials in dysferlinopathy or comparisons with quantitative MRI/S data obtained in other limb‐girdle muscular dystrophy subtypes.